2016
DOI: 10.1038/srep28093
|View full text |Cite
|
Sign up to set email alerts
|

Differential effect of HLA class-I versus class-II transgenes on human T and B cell reconstitution and function in NRG mice

Abstract: Humanized mice expressing Human Leukocyte Antigen (HLA) class I or II transgenes have been generated, but the role of class I vs class II on human T and B cell reconstitution and function has not been investigated in detail. Herein we show that NRG (NOD.RagKO.IL2RγcKO) mice expressing HLA-DR4 molecules (DRAG mice) and those co-expressing HLA-DR4 and HLA-A2 molecules (DRAGA mice) did not differ in their ability to develop human T and B cells, to reconstitute cytokine-secreting CD4 T and CD8 T cells, or to under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
57
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(63 citation statements)
references
References 33 publications
2
57
0
Order By: Relevance
“…Similarly, plasma cell differentiation and the production of IgM, IgA and IgG antibody subtypes is observed, displaying a similar proportion to that observed in humans, but at lower levels than are required for productive antibody responses . Furthermore, it has been reported that HLA‐DR4 mice display increased B‐cell antibody class switching and IgG secretion . Similarly, injection of recombinant human IL‐4 and GM‐CSF before tetanus toxoid immunization stimulates memory B‐cell clonal expansion, induces improved B‐cell class switching capacity and provokes increased total IgG, IgM and tetanus‐specific IgG responses (Table ).…”
Section: Humoral Immunity In Humanized Micementioning
confidence: 72%
See 3 more Smart Citations
“…Similarly, plasma cell differentiation and the production of IgM, IgA and IgG antibody subtypes is observed, displaying a similar proportion to that observed in humans, but at lower levels than are required for productive antibody responses . Furthermore, it has been reported that HLA‐DR4 mice display increased B‐cell antibody class switching and IgG secretion . Similarly, injection of recombinant human IL‐4 and GM‐CSF before tetanus toxoid immunization stimulates memory B‐cell clonal expansion, induces improved B‐cell class switching capacity and provokes increased total IgG, IgM and tetanus‐specific IgG responses (Table ).…”
Section: Humoral Immunity In Humanized Micementioning
confidence: 72%
“…These cells display high polyfunctionality with the ability to produce IFN‐ γ , tumour necrosis factor‐ α , IL‐4 and IL‐17 alongside both granzyme and low levels of perforin . It has also been demonstrated that transgenic mice co‐expressing human HLA‐A2 and HLA‐DR4 did not significantly alter the maturation or development of T‐cell populations; but the HLA‐DR4 single knock‐in mice have an improved polyfunctionality and antigen specificity of effector CD8 + cells over the HLA‐A2 mice . Furthermore, HLA‐DR4 mice have been reported to engraft with high levels of CD4 + CXCR5 + PD1 ++ T follicular helper cells and their subsequent precursors, which are essential in coordinating downstream B‐cell responses.…”
Section: Adaptive Immunity In Humanized Micementioning
confidence: 99%
See 2 more Smart Citations
“…NOD) knocked out for the murine immune system whilst expressing a long-lived functional human immune system (HIS) upon engraftment with human CD34 + hematopoietic stem cells (HSC) from cord blood. 22,23 Both DRAG and DRAGA mice responded by specific antibodies to infection or immunization with malaria protozoans, HIV, ZIKA, malaria protozoan, influenza A/ H1N1 PR8 virus, 24 and scrub typhus. [25][26][27][28] Although various wild-type and humanized mouse models have been described for a number of viral infections (i.e., HIV, EBV, HCV, HBV, HCMV, DENV, HTL-1, HSV-2, HuNoV, JVC, Scrub typhus, ZIKA virus) and bacterial or parasitic infections (i.e., Plasmodium falciparum, Leishmania, Neisseria meningitides, Salmonella Typhi, Borrelia herrmesii, Streptococcus agalactiae group B sepsis, and Scrub Typhus), 18 HIS-humanized animal models for infections with influenza type A infections (IAV) of groups 1 and 2 have not been established yet.…”
Section: Introductionmentioning
confidence: 99%